Pancreatic Duct Cells Isolated From Canines Differentiate Into Beta-Like Pancreatic Islet Cells - Gao, Yuhua; Guan, Weijun; Bai, Chunyu (Frontiers in Veterinary Science, 2022)
In this study, we isolated and cultured pancreatic ductal cells from canines and revealed the possibility for using them to differentiate into functional pancreatic beta cells in vitro. Passaged pancreatic ductal cells were induced to differentiate into beta-like pancreatic islet cells using a mixture of induced factors. Differentiated pancreatic ductal cells were analyzed based on intracellular insulin granules using transmission electron microscopy, the expression of insulin and glucagon using immunofluorescence, and glucose-stimulated insulin secretion using ELISA. Our data revealed that differentiated pancreatic ductal cells not only expressed insulin and glucagon but also synthesized insulin granules and secreted insulin at different glucose concentrations. Our study might assist in the development of effective cell therapies for the treatment of type 1 diabetes mellitus in dogs.